Accomplishing the Public Encounter: A Case for Ethnomethodology in Public Administration Research. Issue 2 (22nd April 2019) - Hand, Laura C; Catlaw, Thomas J
Abstract: Public encounters between street-level bureaucrats and citizens predominantly function through interpersonal interactions. However, there has been relatively little study of the role of talk, what we refer to as language-in-use, in accomplishing the tasks and related objectives within the encounter. This oversight has limited our understanding of the collaborative, negotiated process of public encounters, rendered citizens mostly invisible, and left unexamined the connection between encounters and outcomes. Drawing on the rich but under-utilized tradition of ethnomethodology, a methodology created for studying routine interactions, we provide an analytical example of the language-in-use in one encounter to demonstrate how ethnomethodology is uniquely appropriate for understanding public encounters. We argue that an ethnomethodological approach illuminates the mechanisms that make some outcomes possible, others improbable, and that these accomplishments are important for understanding a variety of outcomes.